The Tibetan assimilation of Buddhism : conversion, contestation, and memory. - Kapstein, Matthew (Oxford University Press, 2000)
This book explores the Buddhist role in the formation of Tibetan religious thought and identity. In three major sections, the author examines Tibet's eighth-century conversion, sources of dispute within the Tibetan Buddhist tradition, and the continuing revelation of the teaching in both doctrine and myth.